2015
DOI: 10.1193/120812eqs347m
|View full text |Cite
|
Sign up to set email alerts
|

Seismic Damage Accumulation in Highway Bridges in Earthquake-Prone Regions

Abstract: Civil infrastructures, such as highway bridges, located in seismically active regions are often subjected to multiple earthquakes, such as multiple main shocks along their service life or main shock-aftershock sequences. Repeated seismic events result in reduced structural capacity and may lead to bridge collapse causing disruption in normal functioning of transportation networks. This study proposes a framework to predict damage accumulation in structures under multiple shock scenarios after developing damage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
34
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 74 publications
(37 citation statements)
references
References 31 publications
(53 reference statements)
0
34
0
Order By: Relevance
“…Both studies quantified damage using a q‐factor (ductility) and compared ductility demand as a function of earthquake loading characteristics, finding that damage accumulation was greater for systems with higher deformation capacities. More recently, Ghosh et al developed a probabilistic framework for assessing damage accumulation in highway bridge columns, using the Park and Ang damage index. The study found that there was a significant increase in damage index exceedance probabilities within each scenario's time frame when multiple events were considered.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Both studies quantified damage using a q‐factor (ductility) and compared ductility demand as a function of earthquake loading characteristics, finding that damage accumulation was greater for systems with higher deformation capacities. More recently, Ghosh et al developed a probabilistic framework for assessing damage accumulation in highway bridge columns, using the Park and Ang damage index. The study found that there was a significant increase in damage index exceedance probabilities within each scenario's time frame when multiple events were considered.…”
Section: Literature Reviewmentioning
confidence: 99%
“…This chapter has been prepared as assemble of previous works published by the authors on topics related to stochastic modeling of damage accumulation. The reader can fi nd some additional details in the following reference documents: Sánchez-Silva and Rackwitz (2004), Bastidas et al (2010), Gosh et al (2012 and Sánchez-Silva and Riascos-Ochoa (2012a,b). The chapter is structured as follows: in Section 15.2 we present an overall description of the deterioration process and the main characteristics of both progressive and shockbased mechanisms.…”
Section: Introductionmentioning
confidence: 98%
“…During the last decade, many researchers have paid their attentions to the effects of seismic sequence or multiple events on the structural performance. Lots of works have been conducted to study the engineering problems related to the MSAS sequences, including ground motion characteristics of MSAS sequences, response spectra of MSAS ground motions, and effects of aftershocks on the damage of multiple degrees of freedoms (MDOF) structures …”
Section: Introductionmentioning
confidence: 99%
“…Zhai comprehensively studied the effects of aftershocks on different kinds of DM s and found that energy‐based DM (ie, normalized hysteretic energy and modified Park‐Ang damage index in this reference) can more effectively reflect the additional damage induced by aftershocks. Several works also used the energy‐based DM to quantify the influences of MSAS sequences on the seismic performance of structure . Besides, residual deformation was used in some works to study the seismic performance of structure under the MSAS sequences.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation